2007
DOI: 10.1097/qai.0b013e318033ffbd
|View full text |Cite
|
Sign up to set email alerts
|

Brief Cognitive Counseling With HIV Testing To Reduce Sexual Risk Among Men Who Have Sex With Men

Abstract: Both interventions were effective in reducing high-risk sexual behavior among MSM repeat testers. PCC participants demonstrated significant behavioral change more swiftly and reported a more satisfying counseling experience than UC participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 17 publications
1
94
0
Order By: Relevance
“…These differences related to addressing the more complex aspects of measuring HIV risk, for example sex role within unprotected sex or partner type. Some studies incorporated aspects of the relationship context of unprotected sex; for example Dilley et al [99][100][101] specifically measured the number of UAI sex episodes with non-primary non-concordant male partners in the previous 90 days. Similarly, Hao et al 103 differentiated between UAI with regular and casual male sex partners.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These differences related to addressing the more complex aspects of measuring HIV risk, for example sex role within unprotected sex or partner type. Some studies incorporated aspects of the relationship context of unprotected sex; for example Dilley et al [99][100][101] specifically measured the number of UAI sex episodes with non-primary non-concordant male partners in the previous 90 days. Similarly, Hao et al 103 differentiated between UAI with regular and casual male sex partners.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…99, Ten RCTs, reported in 11 studies, met the inclusion criteria and were included in the final review. [96][97][98][99][100][101][102][103][104][105][106] A summary of the characteristics of the included studies are shown in Table 2. All studies were conducted in the USA with the exception of one study, which was conducted in China.…”
Section: -106mentioning
confidence: 99%
See 2 more Smart Citations
“…However, some studies have indicated that MSM who test repeatedly have higher levels of risky sexual and drug-use behavior and greater HIV prevalence than MSM who have tested only once (Fernyak et al, 2002;MacKellar et al, 2002;Sifakis et al, 2007). Other research indicates HIV-negative MSM who have tested more than once reduced their sexual risks because of their CT experiences (Dilley et al, 2007;MacKellar et al, 2006). Much is known about the risk factors and behavioral correlates of MSM who repeat test, but less is understood about the characteristics of the very first HIV test experience for this group.…”
mentioning
confidence: 99%